Fluzone® intra-dermal (Intanza®/Istivac® Intra-dermal): An updated overview. Issue 10 (2nd October 2016) - Bragazzi, Nicola Luigi; Orsi, Andrea; Ansaldi, Filippo; Gasparini, Roberto; Icardi, Giancarlo
ABSTRACT: Influenza is a highly contagious respiratory acute viral disease which imposes a very heavy burden both in terms of epidemiology and costs, in the developed countries as well as in the developing ones. It represents a serious public health concern and vaccination constitutes an important tool to reduce or at least mitigate its burden. Despite the existence of a broad armamentarium against influenza and despite all the efforts and recommendations of international organisms to broaden immunization, influenza vaccination coverage is still far from being optimal. This, taken together with logistic and technical difficulties that can result into vaccine shortage, makes intra-dermal (ID) vaccines, such as Fluzone® ID and Intanza®, particularly attractive. ID vaccines are comparable and, in some cases, superior to intra-muscular/sub-cutaneous vaccines in terms of immunogenicity, safety, reactogenicity, tolerability and cross-protection profiles, as well as in terms of patient preference, acceptance and vaccine selection. Further advances, such as Fluzone® ID with alternative B strains and Quadrivalent Fluzone® ID or the possibility of self-administering the vaccines, make influenza ID vaccines even more valuable.